DETERMINAN KEMAUAN MEMBAYAR (WILLINGNESS TO PAY) IURAN JAMINAN KESEHATAN NASIONAL PADA PESERTA MANDIRI DI KOTA JAMBI TAHUN 2021 - Amalia Ane Istamayu; Adila Solida; Rizalia Wardiah (GoAcademica Research dan Publishing, 2022)
This study aims to determine the determinants of willingness to pay national health insurance contributions to independent participants in Jambi City. This study uses a quantitative method with a cross sectional design. The population is all participants of the National Health Insurance (JKN) in 3 sub-districts (East Jambi District, Jambi Market and Jelutung) namely 42,592 participants. The sampling technique used was purposive sampling. The results of this study indicate that there is a relationship between, income, perception of illness and ability to pay contributions with willingness to pay contributions, and there is no relationship between education and the number of family members with willingness to pay contributions.